Disease awareness and healthcare utilization in rural South Africa: a comparative analysis of HIV and diabetes in the HAALSI cohort - Beidelman, Erika T.; Bärnighausen, Till; Wing, Coady; Tollman, Stephen; Phillips, Meredith L.; Rosenberg, Molly (BMC public health, 2023)
Studies from rural South Africa indicate that people living with HIV (PLHIV) may have better health outcomes than those without, potentially due to the frequent healthcare visits necessitated by infection. Here, we examined the association between HIV status and healthcare utilization, using diabetes as an illustrative comparator of another high-burden, healthcare-intensive disease.
Gesehen am 22.01.2024